2007
DOI: 10.1158/1055-9965.epi-07-0313
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity and Sex Hormones in Girls

Abstract: Greater body fatness during childhood is associated with reduced risk of premenopausal breast cancer, but few studies have addressed the relation of adiposity with sex hormones in girls. We prospectively examined associations between adiposity and circulating levels of sex hormones and sex hormone -binding globulin (SHBG) among 286 girls in the Dietary Intervention Study in Children. Participants were 8 to 10 years old at baseline and were followed for an average of 7 years. Anthropometric measurements were ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 65 publications
1
36
1
Order By: Relevance
“…In a 7-year longitudinal study of 286 girls initially ages 8 to 9 years, adiposity was associated with higher circulating concentrations of DHEA sulfate and lower concentrations of sex hormone -binding globulin; however, there were no consistent associations for circulating levels of estrogen or progesterone (34). The lack of an association for estrogen would suggest that early adolescent obesity is not likely to influence postmenopausal breast cancer risk through estrogen signaling, consistent with the similar association for ER+ (RR, 0.80) and ERÀ (RR, 0.77) tumors in our study.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In a 7-year longitudinal study of 286 girls initially ages 8 to 9 years, adiposity was associated with higher circulating concentrations of DHEA sulfate and lower concentrations of sex hormone -binding globulin; however, there were no consistent associations for circulating levels of estrogen or progesterone (34). The lack of an association for estrogen would suggest that early adolescent obesity is not likely to influence postmenopausal breast cancer risk through estrogen signaling, consistent with the similar association for ER+ (RR, 0.80) and ERÀ (RR, 0.77) tumors in our study.…”
Section: Discussionmentioning
confidence: 89%
“…However, the effect of fewer ovulatory cycles could be more pronounced during the time frame before first full-term pregnancy, and particularly in adolescence, due to the greater susceptibility to carcinogens of undifferentiated breast tissue (39,40). There may also be other aspects of the hormonal milieu associated with obesity in the early teenage years that protects against breast cancer, and this requires further evaluation (34,35). Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…Hormonal pathways were suggested as a potential explanation. Childhood and adolescent obesity in girls was found to be associated with increased levels of androgens [28], which may inhibit the maturation of ovarian follicles and reduce the frequency of ovulatory cycles [28]. Anovulation is indeed more common in overweight/obese fertile women [29]; even a BMI of 24 kg/m 2 is associated with higher risk for ovulatory infertility [30,31].…”
Section: Adolescent Overweight and Obesity-premenopausal Bcmentioning
confidence: 99%
“…Some have argued that the association between asthma and overweight could be attributable to less physical activity in women with high BMI, but studies have shown that the association between asthma and obesity is independent of physical activity [23,24] and that obese women with early menarche may have a more severe asthma phenotype [25]. Higher BMI is also associated with higher levels of female sex hormones [26] and systemic inflammation [27]. Leptin, a pro-inflammatory cytokine secreted by adipocytes, is associated with both early menarche [28] and asthma [29].…”
Section: Discussionmentioning
confidence: 99%